THE ANALYSIS OF COULOMB FAILURE STRESS FROM THE 2018 LOMBOK EARTHQUAKE AFTERSLIP AND ITS RELATION TO AFTERSHOCK - Alwi, Muhammad
The 2018 Lombok earthquake was an earthquake with a strength of up to Mw 7.0 which had a significant impact on the Lombok area and its surroundings. After this large earthquake, a series of aftershocks occurred, increasing the risk of further damage. Although much research has been carried out regarding the 2018 Lombok earthquake, research regarding the Coulomb Failure Stress value in the afterslip area of the Lombok earthquake and its relation to the level of seismicity in this area has not yet been studied. This research aims to analyze the Coulomb Failure Stress value on the fault plane after the 2018 Lombok earthquake and investigate its relationship with aftershock events. The correlation between Coulomb Failure Stress and aftershock was carried out to understand the relationship between the two. Numerical modeling was carried out using afterslip field data and aftershock distribution data collected through several previous studies. Modeling results show that the majority of aftershocks after the 2018 Lombok earthquake were not triggered by afterslip fields.